Occupational Stress and Coping Strategies among Female Employees of Commercial Banks in Nigeria (International Journal of Scientific Research and Management (IJSRM), 2017)
This study examines different form of coping strategies adopted by female employees of commercial banks in Akwa Ibom State, South- South, Nigeria. The cross- sectional descriptive survey design was adopted and various coping strategies as they influence occupational stress were examined. Occupational stress and coping strategy questionnaire was used in data collection. Employees’ adoption of both organizational and personal coping strategies was assessed. The population consist of785 female employees of the 18 commercial banks in the Akwa Ibom State. Nine (9) commercial banks were selected randomly by simple random sampling while 365 female employees from the selected banks were randomly selected using stratified random sampling. Occupational Stress and Coping Strategies Questionnaire was developed to elicit data from the respondents. Of the 365 copies of the questionnaire administered, 272 copies were retrieved. Descriptive data were analyzed using frequency and simple percentages while multiple logistic regressions analysis was conducted on the study’s formulated hypotheses. The results of the analysis showed annual leave and getting assistance from colleagues as the most widely used organizational and personal coping strategies respectively. Result of multiple logistic regression analysis revealed that physical activity and getting assistance from colleagues as well as annual leave and job rotation significantly reduced occupational stress while lunch breaks and listening to music while on duty were insignificant. Therefore, there is need for management in commercial banks to increase the level of social support among female employees. Also, sporting/ games facilities such as gym, chess, scrabble, Crèche, Restaurant, Staff bus and Staff quarters should be provided for use by employees so as to assist them cope with occupational stress.